Sánchez Intriago, Isis Kirina(2023)EVALUACIÓN DEL EFECTO DEL PROCESO DE FERMENTACIÓN EN EL PERFIL DE COMPUESTOS NO VOLÁTILES Y FUNCIONALES DE CUATRO MATERIALES DE CACAO ECUATORIANO.Quevedo.UTEQ.84p. - Sánchez Intriago , Isis Kirina (2023)
The determination of the parameters; fat content, total flavonoid content, total polyphenol content and the determination of the fermentation index based on the loss of total polyphenol content, allow the existence of a genotypic differentiation in cocoa (Theobroma cacao. L). This differentiation based on the phytochemical characterization will allow cocoa producers in Ecuador to have a standardized quality tool avoiding cocoa adulteration today, allowing the seller to set a better sale price in the market. For this, these walls were measured in four Ecuadorian cocoa materials of the National and Amazonian type through the statistical analysis of a nested experimental design, to evaluate the effect of the type of material or genotype (Factor A) and the fermentation process (Factor B). on the non-volatile and functional components that are precursors of the Ecuadorian cocoa aroma. Factor A is considered as the main factor and factor B as the nested factor. The results reported that the factor that most influences the variation of data at a confidence level of 95 % is the fermentation time (Factor B), the fourth day of fermentation (96 h) was considered as the optimal day of fermentation, The parameters measured in the investigation reported the following data for each material (EET-95, EET-96, EET-103); fat content 47.35, 45.91, 44.73 and 44.36 % respectively; total flavonoid content 44.51, 42.17, 35.28 and 44.53 mg CE•g-1 respectively; total polyphenol content 106.38, 126.65, 91.03 and 87.54 mg AGE•g-1 respectively and finally in the fermentation index based on the loss of total polyphenols reported values of 49.44, 50.96, 54.17 and 50.19 % respectively.